STUDY OF NICOTIANA TABACUM L EXTRACTION, BY METHODS OF LIQUID AND SUPERCRITICAL FLUID EXTRACTION - Ikhsanov, Yerbol Saginovich; Nauryzbaev, Michael; Musabekova, Altynay; Alimzhanova, Mereke; Burashev, Erlan (Journal of Applied Engineering Science, 2019)
The article presents a comparative analysis of various methods and conditions of extraction from the plant Nicotiana tabacum l, harvested in the Almaty region of the Republic of Kazakhstan in 2018. The study of extracts obtained by the traditional method of solvent extraction in particular hexane, and the method of supercritical fluid extraction, carbon dioxide, under various conditions of the process. Three different supercritical extraction modes were selected, namely: at a relatively low pressure of 120 bar and a low temperature of 28 ° C, at an elevated temperature with the same pressure (60 ° C, 120 bar) and at an elevated temperature and pressure (80 ° C , 170 bar). As a result of studying the obtained extracts by GC-MS, their qualitative and quantitative composition was identified. It has been established that the largest number of various compounds is extracted by supercritical fluid extraction at a relatively low pressure of 150 bar for this method and a low temperature of 28 ° C, but the most popular compound in the studied raw material, nicotine, is extracted with approximately the efficiency similar to the classical method. To increase the yield of the target component, the extraction conditions were changed. As a result, a significant increase in the degree of extraction of the target product was achieved under the following conditions: pressure 120 bar, temperature 60 ° C. Under these conditions, the degree of extraction was 47.40%. Conducted to control and more fully study the laws of the extraction process (at elevated pressure) showed less efficiency, only 12.29%. This result is lower in efficiency than the classical extraction method. From the data obtained, it follows that for the extraction of nicotine, a substance belonging to the class of alkaloids and which is resistant to thermal destruction, preferred and most effective, is the mode of supercritical extraction at a temperature of 60 ° C and a pressure of 120 bar.